DPP4 inhibition attenuates filtration barrier injury and oxidant stress in the Zucker obese rat - Nistala, Ravi (2014)
OBJECTIVE: Obesity-related glomerulopathy is characterized initially by glomerular hyperfiltration with hypertrophy and then development of proteinuria. Putative mechanisms include endothelial dysfunction and filtration barrier injury due to oxidant stress and immune activation. There has been recent interest in targeting dipeptidyl peptidase 4 (DPP4) enzyme due to increasing role in non-enzymatic cellular processes. METHODS: We utilized the Zucker obese (ZO) rat, (aged 8 weeks) fed a normal chow or diet containing the DPP4 inhibitor linagliptin for 8 weeks (83mg/kg rat chow). RESULTS: Compared to lean controls, there were increases in plasma DPP4 activity along with proteinuria in ZO rats. ZO rats further displayed increases in glomerular size and podocyte foot process effacement. These findings occurred in parallel with decreased endothelial stromal-derived factor-1α (SDF-1α), increased oxidant markers, and tyrosine phosphorylation of nephrin and serine phosphorylation of the mammalian target of rapamycin (mTOR). DPP4 inhibition improved proteinuria along with filtration barrier remodeling, circulating and kidney tissue DPP4 activity, increased active glucagon like peptide–1 (GLP-1) as well as SDF-1α, and improved oxidant markers and the podocyte-specific protein nephrin. CONCLUSIONS: These data support a role for DPP4 in glomerular filtration function and targeting DPP4 with inhibition improves oxidant stress-related glomerulopathy and associated proteinuria.